Cardiovascular Magnetic Resonance Provides Evidence of Abnormal Myocardial Strain and Primary Cardiomyopathy in Marfan syndrome. Issue 3 (May 2019) - Winther, Simon; Williams, Lynne K.; Keir, Michelle; Connelly, Kim A.; Bradley, Timothy J.; Rakowski, Harry; Crean, Andrew M.
Abstract : Objective: Marfan syndrome is an autosomal-dominant genetic disorder caused by mutations in the fibrillin-1 gene. The condition is a connective tissue disease that frequently involves the cardiovascular system. The existence of a primary cardiomyopathy in Marfan syndrome, however, is controversial. The aims of this study were to investigate the prevalence of left ventricular dysfunction with both transthoracic echocardiography and cardiovascular magnetic resonance (CMR) in a cohort of Marfan syndrome patients and to investigate patterns of myocardial strain across the cohort. Methods: We used an institutional database to identify all patients with a firm diagnosis of Marfan syndrome based on Ghent criteria. Inclusion required left ventricular ejection fraction (LVEF) to have been measured by both CMR and transthoracic echocardiography within 12 months of each other. Normal LVEF was defined as a value of >55% when measured by CMR. Velocity vector imaging was used to measure left ventricular longitudinal strain patterns by application of feature tracking to cine magnetic resonance images. Results were compared with data from 20 age-matched control subjects. Results: Sixty-nine Marfan syndrome patients met the inclusion criteria. The mean age was 35.4 ± 15.0 years, and 56.5% were male. The mean LVEF was 59.0% ± 7.0% by CMR and 59.1% ± 5.8% by echo. One-fifth of Marfan syndrome patients (15/69; 21.7%) had reduced function with LVEF ⩽55% by CMR, but only 5 of these were identified by echo. Furthermore, echo identified 5 Marfan syndrome patients as having reduced LVEF in the presence of a normal LVEF by CMR. Some Marfan syndrome patients had abnormal longitudinal strain patterns even with LVEF within the reference range. Conclusions: These data provide support for a primary cardiomyopathy in some Marfan syndrome patients. Cardiovascular magnetic resonance is more sensitive than echo for identifying cases with mild systolic dysfunction. Strain analysis may be more sensitive than simple LVEF assessment for identifying at-risk individuals. Abstract : Supplemental digital content is available in the text.